Simeon the God-Receiver (Luke 2:21–35) as a Translator of the Septuagint: Investigating the Sources of a Popular Hagiographic Legend in Orthodox Christianity - Oancea, Constantin (Religions, 2024)
The legend of the old man Simeon, who received Jesus in his arms and was one of the Septuagint translators, is almost unknown in Western Christianity but is very popular today among Orthodox Christians. The version circulating in Orthodox churches is based on the account in Demetrius of Rostov’s Lives of the Saints. The article explores the occurrences of the legend in modern, medieval Slavonic, Byzantine, and oriental writings and attempts to identify the stages of the transmission of the legend from antiquity to modern times. The historical analysis and the comparison of the motifs found in these writings make the hypothesis of a Byzantine archetype of the legend plausible. This writing has been lost, but it was previously translated into Syriac, Arabic, and Slavonic, contributing to the spread of the legend in Eastern and Slavic Christianity. The legend builds on the identification of Simeon in Luke’s Gospel with Shimʿon ha-Tsaddiq. It interprets Luke 2:26 by constructing a pre-history of the episode that places Simeon into the time of the Septuagint translation. The miracle of prolonging Righteous Simeon’s life functions as a reconfirmation of the fundamental character of Isaiah 7:14 for Christianity.